2019
DOI: 10.1055/s-0039-1679921
|View full text |Cite
|
Sign up to set email alerts
|

Primary Total knee Arthroplasty: A Viable Surgical Option for Complex Tibial Plateau Fractures in Elderly

Abstract: The optimal treatment of complex tibial plateau fractures in elderly is still controversial. The aim of the study was to retrospectively analyze the clinical and radiological outcomes of primary total knee arthroplasty (TKA) versus open reduction and internal fixation (ORIF) in elderly patients presenting with acute complex tibial plateau fractures. Between June 2011 and December 2015, we have analyzed the clinical outcomes of 22 primary total knee replacements and 21 ORIFs. The mean follow-up was 27 months. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 45 publications
0
12
0
2
Order By: Relevance
“…Pasurka et al reported that patients with primary TKR achieved independent mobility earlier than patients treated with ORIF [29]. In both studies, complication and reoperation rates were also lower in the primary TKR group [29,36].…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Pasurka et al reported that patients with primary TKR achieved independent mobility earlier than patients treated with ORIF [29]. In both studies, complication and reoperation rates were also lower in the primary TKR group [29,36].…”
Section: Discussionmentioning
confidence: 90%
“…months)[12,16,[21][22][23][24][25][26][27][34][35][36][37]. Studies using the AO classification identified seven A-type (1%), 70 B-type (65%) and 31 C-type (39%) tibia fractures in a total of 108 patients[21, 23, 25-27, 29, 34, 37].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Plateau tibia fractures are high-energy injuries that can cause poor functional outcomes if not properly treated [9,10]. There are several ways to treat these fractures, including traction and cast braces, external fixation extending across the knee, percutaneous fixation and restricted open reduction, internal fixation and open reduction, and indirect reduction and stabilization with hybrid or circular external fixation devices [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, faster discharge from the hospital can help to limit the disorientation often observed in this elderly population. 6 – 17 The goal of this literature review is to give an overview of current indications, treatment strategies, surgical pitfalls, post-operative management and results to be expected.…”
Section: Introductionmentioning
confidence: 99%